Salt-sensitive increase in macrophages in the kidneys of Dahl SS rats - Fehrenbach, Daniel J. (Am J Physiol Renal Physiol, 2019)
Studies of Dahl salt-sensitive (SS) rats have shown that renal CD3(+) T cells and ED-1(+) macrophages are involved in the development of salt-sensitive hypertension and renal damage. The present study demonstrated that the increase in renal immune cells, which accompanies renal hypertrophy and albuminuria in high-salt diet-fed Dahl SS rats, is absent in Sprague-Dawley and SSBN13 rats that are protected from the SS disease phenotype. Flow cytometric analysis demonstrated that >70% of the immune cells in the SS kidney are M1 macrophages. PCR profiling of renal myeloid cells showed a salt-induced upregulation in 9 of 84 genes related to Toll-like receptor signaling, with notable upregulation of the Toll-like receptor 4/CD14/MD2 complex. Because of the prominent increase in macrophages in the SS kidney, we used liposome-encapsulated clodronate (Clod) to deplete macrophages and assess their contribution to salt-sensitive hypertension and renal damage. Dahl SS animals were administered either Clod-containing liposomes (Clod-Lipo), Clod, or PBS-containing liposomes as a vehicle control. Clod-Lipo treatment depleted circulating and splenic macrophages by ∼50%; however, contrary to our hypothesis, Clod-Lipo-treated animals developed an exacerbated salt-sensitive response with respect to blood pressure and albuminuria, which was accompanied by increased renal T and B cells. Interestingly, those treated with Clod also demonstrated an exacerbated phenotype, but it was less severe than Clod-Lipo-treated animals and independent of changes to the number of renal immune cells. Here, we have shown that renal macrophages in Dahl SS animals sustain a M1 proinflammatory phenotype in response to increased dietary salt and highlighted potential adverse effects of Clod-Lipo macrophage depletion.